Sizing and Eddy currents in magnetic core nanoparticles: An optical extinction approach - Mendoza Herrera, Luis Joaquin (2016)
Optical extinction is a handy and ubiquitous technique that allows us to study colloidal nanoparticles in their native state. The typical analysis of the extinction spectrum can be extended in order to obtain structural information of the sample such as the size distribution of the cores and the thickness of the coating layers. In this work the extinction spectra of Fe3O4, Fe3O4@Au, and Fe3O4@SiO2@Au single and multilayer nanoparticles are obtained by solving full Mie theory with a frequency dependent susceptibility derived from the Gilbert equation and considering the effect of Eddy currents. The results are compared with non-magnetic Mie theory, magnetic dipolar approximation and magnetic Mie theory without Eddy currents. The particle size-wavelength ranges of validity of these different approaches are explored and novel results are obtained for Eddy current effects in optical extinction. These results are used to obtain particle size and shell thickness information from the experimental extinction spectra of Fe3O4 and Fe3O4@Au nanoparticles in good agreement with TEM results, and to predict the plasmon peak parameters for Fe3O4@SiO2@Au three layer nanoparticles.